Educational Pearls Behind The Phase Of Birth And Forty Years Before Prophethood (Reinterpretation Of The Prophetic Head By Sheikh Shafiyyurrahman Al-Mubarakfuri) - Hendrikus Maku (LPPM Universitas PGRI Sumatera Barat, 2023)
If in the clouds there is always water that will fall to wet the barren earth, this is also the case with every story in the sirah nabawiyah. The aim of this research is to find educational pearls behind every story or event. There are two methods that will be used in this research, namely: first, using